Transformation in the architectural identity of palaces - Nurul Alia Ahamad,; Zahari Zubir,; Prince Favis Isip,; Nor Hayati Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The establishment of the first National Palace in Malaya in 1957 reflects the transformation in the identity of palace architecture. Traditional palace architecture has developed from society’s traditional way of life, as well as the materials and techniques of local construction. However, in the 1950s, significant changes could be seen in the lifestyle, politics, economics and many other areas in Malaya due to modernisation. The changes in the political system and people’s values have influenced the traditional palace architecture during the 1950s. This research aims to highlight the palace’s architecture transformation as direct consequences of changes in the identity of the state and nation. The research employs interpretive historical methodology, with the first National Palace as the case study. The study concluded that the architecture of the first National Palace reflects an image based on the contemporary values of the local community, which meet the political aspiration of a modern democratic government at that time. These findings will contribute to the understanding of the changes in the traditional social contract between the rulers and the people, and the selection of modern architecture as an identity of the country’s current government.